Sanções processuais por improbidade na execução civil - Ligero, Gilberto Notário (2014)
This thesis has as its object the procedural sanctions for misconduct in civil enforcement. The methodological approach, observing the concentration area of the program is given by the fact that currently the executive activity, represented by the execution of a sentence or the autonomous process execution, is considered essential to the effectiveness of judicial protection . What happens is that some factors have influenced the performance of this type of lawsuit. Among the factors is the disrespect, strong and steady, the duties of procedural fairness in executive screen. The attacks on the dignity of Justice earn several ways: disrespect for the court order to indicate the goods are seized, the challenge and fulfillment of sentence manifestly dilatory embargoes, fraud enforcement, disposition of property seized, bringing undue executions, abuse of the right of registration certificate of the distribution of execution, etc. To sanction the creditor and the debtor, the system adopts the protective-repressive pattern of conduct discouraging, materializing through the fines and the obligation to repair damage. The legislature of little worth premiais sanction measures whose purpose is to promote encouraging conduct. By analyzing the structure of the disciplinary system in CPC / 73, it appears that the same is not meeting your functional expectations: to punish and educate. The revisiting of concepts and ideas is essential to building a new concept of procedural sanction, based on constructivist pedagogical interactionism. This new ideal penalty is established because of the need for transformation of the procedural subjects pipelines. In most, sees the need to expand the list of penalties, turning the research at this point for the implementation of restrictive measures of rights, which are sparse in the legislation. Thus defends the imposition of such sanctions as atypical modes in addition to the typical. The judge with their explicit and implicit powers and duties can take advantage of these measures. Given the normative principle of proportionality, by variants of the necessity and appropriateness, the judge can apply them, without, however, undermining fundamental rights. In addition to the restrictive sanctions, the system needs to incorporate positive measures (premiais), to meet their ends, so that makes the proposal of a prize for those who litigarem responsibly. It is proposed for the effective adoption of these measures, a bill changer law of the CPC. Then defends the idea in the sense that a significant structural change must occur in the sanctioning system, for that unfair and bad faith practices are transformed into probas practices. The deductive method is with the use of technical analysis of relevant literature and case law related to